Pengaruh Leverage dan Profitabilitas Terhadap Nilai Perusahaan pada Perusahaan Sub Sektor Farmasi yang Terdaftar Di Bursa Efek Indonesia Periode 2015-2019 - issomatusaada issomatusaada; Dian Nirmala Dewi; Anita Kusuma Dewi (Jurnal Ilmiah ESAI, 2022)
This study aims to determine the effect of leverage and profitability on firm value. This research uses purposive sumpling technique. The population used in this study were 10 companies producing 6 samples based on predetermined criteria. This study uses secondary data from the Indonesia Stock Exchange website, SahamOk, in the form of finance reports and annual reports. Data analysis used classical assumption test, multiple linear analysis test, and t test. Leverage variables used in this study are Debt to Equity Ratio (DER) and Debt Ratio (DR). Profitability variables used in this study are Return On Equity (ROE) and Earning Per Share (EPS). The firm value variable in this study uses Tobin's Q. The results show that ROE and EPS have an effect on firm value but the DER and DR variables have no effect.